2021
DOI: 10.1021/acs.orglett.1c02754
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Promoted (4 + 1) Annulation of Isocyanoacetates with Alkylpyridinium Salts: Divergent Regioselective Synthesis of 1,2-Disubstituted Indolizines

Abstract: An unprecedented silver-promoted regioselective (4 + 1) annulation of isocyanoacetates with pyridinium salts is reported. The established protocol provides controlled, facile, and modular access to a range of synthetically useful N-fused heterocyclic scaffolds containing indolizines, pyrrolo[1,2-a]quinolines, pyrrolo[2,1-a]isoquinolines, and 1H-imidazo[4,5-a]indolizin-2(3H)-ones. A mechanistic pathway involving nucleophilic addition/protonation/elimination/cycloisomerization is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In this context, we recently reported that 2-(2-bromophenyl)-1Hbenzo [d]-imidazole derivatives can be harnessed as an effective coupling partner in combination with 2-bromobenzoic acids to give the corresponding N-fused (benzo)imidazophenanthridine scaffolds in high yields. 16 In continuation of our previous studies directed to transition-metal-assisted synthesis of heterocycles, 17 we envisaged that phenanthridin-6(5H)-one derivatives could be directly assembled from N-substituted 2bromobenzamides 1 and 2-bromobenzoic acids 2 in the presence of a metal catalyst (Figure 1, bottom).…”
Section: ■ Introductionmentioning
confidence: 80%
“…In this context, we recently reported that 2-(2-bromophenyl)-1Hbenzo [d]-imidazole derivatives can be harnessed as an effective coupling partner in combination with 2-bromobenzoic acids to give the corresponding N-fused (benzo)imidazophenanthridine scaffolds in high yields. 16 In continuation of our previous studies directed to transition-metal-assisted synthesis of heterocycles, 17 we envisaged that phenanthridin-6(5H)-one derivatives could be directly assembled from N-substituted 2bromobenzamides 1 and 2-bromobenzoic acids 2 in the presence of a metal catalyst (Figure 1, bottom).…”
Section: ■ Introductionmentioning
confidence: 80%
“…Later, Liu, Kärkäs and Wang's group reported a silver‐promoted regioselective [4+1] annulation of pyridinium salts 201 with isocyanoacetates 202 , which provided controlled and modular access to two types of 1,2‐disubstituted indolizinesindolizines 203 and 204 in good to excellent yields (Scheme 25a) [37] . In this reaction, the generation of final products depended on the amount of the silver salt, the solvent, and the temperature.…”
Section: Synthesis Of Fused Cyclic Compoundsmentioning
confidence: 99%
“…During their synthetic programme, Kärkäs, Wang and co-workers developed an unprecedented [4+1] annulation of alkylpyridinium/quinolium salts with isocyanoacetates which provided two kinds of 1,2-disubstituted indolizines in good to excellent yields. 58…”
Section: Reaction With Isocyanoacetatesmentioning
confidence: 99%
“…During their synthetic programme, Kärkäs, Wang and co-workers developed an unprecedented [4+1] annulation of alkylpyridinium/quinolium salts with isocyanoacetates that provided two kinds of 1,2-disubstituted indolizines in good to excellent yields. 58 They observed that the reaction of 1-(2-oxo-2-arylethyl)pyridinium bromides 80 with isocyanoacetate 81 in the presence of Ag 2 CO 3 in DMF afforded isocyano substituted indolizine 82 (Scheme 21). The use of the corresponding quinoline salts resulted indolizine carboxylate derivative 83.…”
Section: Reaction With Isocyanoacetatesmentioning
confidence: 99%